Copper(I) O,O '-dialkyldithiophosphate clusters: EXAFS, NMR and X-ray diffraction studies - Rusanova, D; Christensen, K; Persson, I; Pike, K; Antzutkin, O; Zou, X; Dupree, R; Forsling, W (2007)
Copper K-edge EXAFS data for six polycrystalline cubic cluster compounds, {Cu8[S2P(OR)2]6(μ8-S)} with R = Et, nPr, iPr, nBu, iBu and iAm, show that the architecture of their Cu8(S2P)2S cores is fairly rigid and independent of both length and branching of the alkyl chain, and that the structure of the cluster is maintained in acetone solution. Solid-state 31P CP-MAS and static 65Cu NMR data for {Cu8[S2P(OnPr)2]6(μ8-S)} and {Cu8[S2P(OEt)2]6(μ8-S)} show similarities in the icosahedral O,O′-dialkyldithiophosphate shells and in the 'cubic' copper cores in these cluster compounds. The crystal structure of {Cu8[S2P(OnPr)2]6(μ8-S)} was resolved using single-crystal X-ray diffraction. © 2007 Taylor and Francis.